ANALISIS PENERAPAN NILAI KARAKTER PADA PEMBELAJARAN KURIKULUM 2013 KELAS IV GUGUS III KECAMATAN SAIL PEKANBARU - Afrina Putri Kazain; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Data analysis technique used is through the test of validity by expert value of character and expert on curriculum learning, in that case validated by Dr. Hambali, M. Si and Dr. Charlina, M. Hum. While the data analysis in this study, researchers collect test results, correct and give scores, then calculate the average of the research. In the subtheme of togetherness and diversity, in the implementation of learning, found the teacher develops the value of religious character, honest, tolerance, discipline, curiosity, and responsibility to learners. While on the occurrence of character values in children through questionnaires are distributed when the subtheme togetherness of diversity takes place with the percentage of religious gain 75.6%, tolerance 74.6%, discipline 73.6%, care 73.2%, honest 72.2% , and 67.1% responsibility. Then on the grateful subthemes of diversity found the teacher develops the value of religious character, honest, tolerance, discipline, curiosity, environmental care, social care, and responsibility to learners. With the acquisition percentage of religious 75,5%, tolerance 68,2%, discipline 70%, care 71%, honest 74,8%, and responsibility 66,2%. Furthermore, on the subtheme of energy sources, found the teacher develop the value of religious character, honest, tolerance, discipline, curiosity, environmental care, social care, and responsibility. with the percentage gain is religious 72,6%, tolerance 66,1%, discipline 68,4%, caring 68,6%, honest 72,1%, and responsibility 64,4%. Then on the subtheme of my nation's cultural diversity, it was found that teachers developed values of religious character, honesty, tolerance, discipline, curiosity, environmental care, social care, and responsibility. With the percentage of religious gain 76,5%, tolerance 75,4%, discipline 70,7%, caring 70,2%, honest 68,2%, and responsibility 62,3%. Based on the analysis of the research, it can be concluded that the implementation of the 2013 curriculum learning as a whole has implemented seven character values, in accordance with the Minister of Education and Culture Regulation no. 64 Year 2013, on Basic and Secondary Education Content Standards. The values of these characters are religious, honest, disciplined, responsible, caring, polite, and confident. The character values that appear in the learning of the 2013 curriculum by students, based on the questionnaire that has been disseminated, are mostly developed in childrenKeywords: Value of character, learning curriculum 2013.